PECULIARITIES OF VALUES OF MILITARY SERVANTS OF THE NATIONAL GUARD OF UKRAINE - Matsehora, Yanina; Prikhodko, Ihor; Kolesnichenko, Oleksandr (Honor and Law, 2022)
The events after February 24, 2022 showed the extraordinary rise of the fighting spirit of the Security and Defense Forces of Ukraine, the consolidation of all Ukrainian society around this social group and its values for the preservation of Ukrainian society and its way of life. Under such circumstances, the values of servicemen emphasized the function of determining the role of servicemen in society, which contributed to the transition to the level of semantic regulation of the professional activity of servicemen. Translating military values into meaning opens the way to extremely large resources to maintain the professional activity of servicemen. The study showed that the values of the National Guard of Ukraine are an extremely important element in the formation of both individual style of professional activity and group interaction, which, being focused on achieving socially important results, can overcome individual shortcomings, both at the level of individual functioning and at the level of group functioning (based on openness). It is determined that the values ensure the cohesion of the military team and the reliability of its functioning as a whole and its key actors (military leaders), given the specifics of their role in the team (activation, enforcement of orders for sergeants and non-commissioned officers; military staff for officers; responsibility for the consequences of military decisions for senior officers). The unity of values ensures the formation of trust between subordinates and military leaders. The introduction of a formalized code of ethics for servicemen of the National Guard of Ukraine, its study and understanding of the content of generalized military values should allow to form the unity of values in the military teams of the National Guard of Ukraine.